Abrahamic traditions and egg freezing: Religious Women's experiences in local moral worlds - Inhorn, Marcia C.; Birenbaum-Carmeli, Daphna; Vale, Mira D.; Patrizio, Pasquale (Social science & medicine (1982), 2020)
In this article, we elucidate how elective egg freezing (EEF) has been received within the three Abrahamic traditions—Judaism, Christianity, and Islam—and how these religion-specific standpoints have affected the EEF experiences of women who self-identify as religiously observant. Through an analysis of religious women's narratives, the study explores the “local moral worlds” of religious women who chose to freeze their eggs for non-medical reasons. It draws on ethnographic interviews with 14 women in the United States and Israel who had completed at least one EEF cycle, and who were part of a large, binational study that interviewed, between 2014 and 2016, 150 women who pursued EEF. These religious women, who were all highly educated, faced a particular challenge in finding appropriate marriage partners. Feeling pressured but still hopeful to marry and create large families, the women used EEF to extend their reproductive timelines and reduce their anxieties. As the study showed, the women reinterpreted or reconciled religious restrictions on the use of EEF in various ways, believing that their ultimate pursuit of religiously sanctioned reproduction justified the means. This study, which is the first to compare Jewish, Christian, and Muslim women's experiences of EEF, illustrates how this novel technology is now shaping the local moral worlds of religious women. •Abrahamic religious traditions demonstrate support for elective egg freezing (EEF).•Catholicism is the exception, prohibiting EEF for fertility preservation.•Religious women are turning to EEF when they cannot find a marital partner.•EEF extends reproductive timelines and reduces religious women's anxieties.•Religious women transgress EEF restrictions to accomplish future motherhood goals.